Diarrheal disease outbreak in Muskkot, Gulmi, Nepal – 2019 - Pachya, Uttam (Journal of General Practice and Emergency Medicine of Nepal, 2019)
Introduction: Diarrhea disease outbreak was observed in Dajakot, Musikot Municipality, Gulmi, Nepal on April 2019. This study analyzes the data that were collected during this outbreak. Method: This is a descriptive, cross sectional study defining the diarrheal outbreak at Gulmi in time, place and person. Result: There were 188 patients presenting with symptom of diarrhea from April 23 to 29, 2019. There were 108 (57.4%) female and 80 (42.5%) male. Maximum (69) number of patients were on day 3 of outbreak. Conclusion: The outbreak observed at Musikot in 2019 was due to contaminated source of water.